Ethical and legislative advances in xenotransplantation for clinical translation: focusing on cardiac, kidney and islet cell xenotransplantation - Hawthorne, Wayne J. (Frontiers in Immunology, 2024)
IIn this state-of-the-art review we detail the journey of xenotransplantation from its infancy, detailing one of the first published cases and the subsequent journey the field took in its inception and development. With a focus on the science, technological advances, precautions required along with the potential limitations in application, the ethics, guidance’s, and legislative advances that are required to reach the safe and efficacious clinical application of xenotransplantation. Along with a view over the past several decades with the overall significant advancements in pre-clinical study outcomes particularly in islet, kidney, and heart xenotransplantation, to ultimately reach the pinnacle of successful clinical heart and kidney xenotransplants. It outlines the importance for the appropriate guidance’s required to have been developed by experts, scientists, clinicians, and other players who helped develop the field over the past decades. It also touches upon patient advocacy along with perspectives and expectations of patients, along with public opinion and media influence on the understanding and perception of xenotransplantation. It discusses the legislative environment in different jurisdictions which are reviewed in line with current clinical practices. All of which are ultimately based upon the guidance’s developed from a strong long-term collaboration between the International Xenotransplantation Association, the World Health Organisation and The Transplantation Society; each having constantly undertaken consultation and outreach to help develop best practice for clinical xenotransplantation application. These clearly helped forge the legislative frameworks required along with harmonization and standardization of regulations which are detailed here. Also, in relation to the significant advances in the context of initial xeno-kidney trials and the even greater potential for clinical xeno-islet trials to commence we discuss the significant advantages of xenotransplantation and the ultimate benefit to our patients.